(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Religion, according to Vivekananda, is in essence man’s way of living in the name of truth. It is quite clear that every recognized religion has three concepts. First is philosophy, second, mythology and the third is rituals. Some gave more emphasis on one and some on other aspect but, obviously, at the heart of every religion was its philosophy and metaphysics which, in the words of Vivekananda himself, presents the whole scope of religion, setting forth its basic principles, its goal, and the means of reaching that goal.